Analysis of School Policies in Handling Bullying through Learner Management and Strengthening Positive Culture in Elementary Schools - Ummah, Nafidatul; Widiyanah, Ima; Hazin, Mufarrihul; Purwoko, Budi (Universitas Muhammadiyah Gorontalo, 2025)
Bullying in primary schools is a social problem that can disrupt learners' psychological and academic development. Effective handling of bullying requires an approach that involves school policies, learner management, and strengthening positive culture in the school environment. The purpose of this study is to analyze the role of school policies in tackling bullying, focusing on the integration of learner management and the establishment of a positive culture as preventive and responsive measures against bullying behavior. This research uses the literature review method, by examining various scientific sources involving education policy, student behavior management, and the role of school culture in creating a safe and inclusive environment. The results of the analysis show that clear and structured school policies, accompanied by learner management based on character building and behavior monitoring, play an important role in preventing bullying. In addition, the positive culture instilled through the values of empathy, tolerance and togetherness also strengthens efforts to prevent and overcome bullying in elementary schools. This study concludes that the successful handling of bullying in primary schools depends not only on the formal policies implemented, but also on the implementation of learner management integrated with a positive school culture. Therefore, a holistic and synergistic approach is needed between policies, learner management, and school culture in shaping a learning environment free from violence and social violence.